System of activities to strengthen Environmental Education for Sustainable Development in 7th1 students from José Ramón León Acosta Junior High School through the teaching-learning process of the English subject - Yanes García, Hanser Leonel (Universidad de Ciencias Pedagógicas "Félix Varela Morales", 2015)
The earth‘s environment is in crisis mainly because it is being abused beyond its capacity by human beings. The present major paper assesses the need for environmental education in the present times. It focuses on the role of teachers to spread awareness of environmental issues and problems. The emphasis is on sensitizing the student community through their teachers who can play a pivotal role in transmitting the requisite knowledge, skills, attitudes and values, essential to restore or at least mitigate the irreversible damage being caused to the environment. The research is inserted in the teaching-learning process of the English subject in 7th graders from José Ramón León Acosta Junior High School. The paper describes a system of communicative activities to strengthen Environmental Education for Sustainable Development in 7th grade students. Different methods from the theoretical, empirical and mathematic levels were used along the process of research. With the partial implementation of the proposal, positive changes were observed in the students in the cognitive and attitudinal dimensions.

L'environnement de la terre est en crise, principalement parce qu'il est maltraité delà de sa capacité par des êtres humains. Le document présent majeur évalue la nécessité pour l'éducation environnementale dans les temps présents. Il se concentre sur le rôle des enseignants pour faire connaître les questions et les problèmes environnementaux. L'accent est mis sur la sensibilisation de la communauté à travers leurs enseignants qui peuvent jouer un rôle essentiel dans la transmission des connaissances, les aptitudes, les attitudes et les valeurs étudiant, essentielle pour restaurer ou au moins atténuer les dommages irréversibles causés à l'environnement. L'enquête est insérée dans le processus du sujet anglais en 7e année de José Ramón León Acosta école secondaire enseignement-apprentissage. Le document décrit un système d'activités communicatives pour renforcer l'éducation environnementale pour le développement durable dans les élèves de 7e. Différentes méthodes des niveaux théoriques, empiriques et mathématiques ont été utilisés au long du processus d'enquête.
Keywords: Lenguas Extranjeras; Inglés; Sistema de Actividades; Secundaria Básica